Proceedings of the International Conference on Psychological Studies (ICPSYCHE 2020) 2021
DOI: 10.2991/assehr.k.210423.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurofeedback Training on Anxiety Symptoms Among University Students

Abstract: Previous studies reported that university students are a population at risk of that mental health problems. The most common intervention for anxiety disorders are pharmacological and/or nonpharmacological strategies such as psychotherapies. Besides that, there is a growing interest neurofeedback training for various mental health conditions including depression, Post Traumatic Stress Disorder (PTSD), stress and anxiety. Therefore, the objective of this study is to determine the effectiveness of neurofeedback t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, it is important to note that this statistic may not fully capture the true extent of anxiety in Malaysia, as many cases go undiagnosed and unreported. Specifically, a recent study involving 1,821 university students across Malaysia revealed that the prevalence of anxiety among this population was as high as 29% (Mutang et al, 2021). This trend of high anxiety prevalence among university students is not unique to Malaysia, as studies conducted globally have shown similar findings (Lim et al, 2022;Mutang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it is important to note that this statistic may not fully capture the true extent of anxiety in Malaysia, as many cases go undiagnosed and unreported. Specifically, a recent study involving 1,821 university students across Malaysia revealed that the prevalence of anxiety among this population was as high as 29% (Mutang et al, 2021). This trend of high anxiety prevalence among university students is not unique to Malaysia, as studies conducted globally have shown similar findings (Lim et al, 2022;Mutang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Specifically, a recent study involving 1,821 university students across Malaysia revealed that the prevalence of anxiety among this population was as high as 29% (Mutang et al, 2021). This trend of high anxiety prevalence among university students is not unique to Malaysia, as studies conducted globally have shown similar findings (Lim et al, 2022;Mutang et al, 2021). Anxiety disorders often have their onset during adolescence, a crucial period of development.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Patients will receive two sessions per week over a course of 7 weeks. This is based on previous studies that demonstrated significant success with a frequency of two sessions per week 24–26. A last follow-up session will be conducted after 2 months.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This is based on previous studies that demonstrated significant success with a frequency of two sessions per week. [24][25][26] A last follow-up session will be conducted after 2 months. The manual comprises the NFB training sessions, the educational session and the diagnostic session to guarantee a standardised procedure for all 14 sessions.…”
Section: Intervention: Manualised Neurofeedback Trainingmentioning
confidence: 99%
“…Psychometric measures were used to assess anxiety, including the State-Trait Anxiety Inventory (STAI), the Sport Anxiety Scale-2 and the General Anxiety Disorder-7, along with measures of sports performance and mental resilience in sport. The authors found that both participants showed significant improvements in their mental resilience, including a greater sense of confidence, perseverance, and control, as well as that, thanks to this training, sport-related anxiety symptoms and general anxiety decreased significantly [ 54 ].…”
Section: Neurofeedback and Target-precision Sportsmentioning
confidence: 99%